INFLUENCE OF THE PUN1 GENE ON CAPSAICIN SYNTHESIS IN HYBRID LINES OF THE GENUS CAPSICUM - T. Srebcheva; M. Kostova (Trakia Journal of Sciences)
The fruits of the Capsicum genus plants are valued for their spicy taste, unique only to them, due to the capsaicin alkaloid and its analogs, named capsaicinoids. Capsaicinoids are absent in sweet peppers, which are sometimes preferred due to the lack of pungency. Their presence or absence is a genetically controlled process, and many of the genes that affect capsaicin synthesis are known. The Pun1 gene plays a lead, and mutations in this locus are the most common cause of loss of pungency in the three related species Capsicum annuum, Capsicum chinense, and Capsicum frutescens. In the present study, we analyzed the effect of the Pun1 gene on the synthesis of capsaicin in hybrid lines of the genus Capsicum. This analysis was performed by comparing the fruit spiciness profile (determined organoleptically) and the allelic state of the Pun1 gene (determined by PCR reaction, using allele-specific primers). The comparative analysis confirms our hypothesis that the pungent and lack of pungent in the selected hybrid lines is entirely controlled by the action of this Pun1 gene only.